Clinical characteristics and management of dasatinib-induced chylothorax: retrospective analysis based on case reports - Liu, Ya; Huang, Ying; Guo, Jincai; Liu, Xiang; Hu, Yixiang (Frontiers in Pharmacology, 2025)
BackgroundDasatinib-induced chylothorax is a rare but potentially serious complication, and its clinical features remain poorly defined. This study aimed to systematically evaluate its clinical characteristics, therapeutic approaches, and patient outcomes to provide practical guidance for clinical management.MethodsWe conducted a retrospective analysis by systematically retrieving case reports of dasatinib-induced chylothorax from relevant databases up to 31 May 2025, to achieve a comprehensive assessment.ResultsA total of 24 patients from 22 published case reports and case series were included in this analysis. The median age was 50 years (range 5, 79), and the median time to onset of chylothorax following dasatinib initiation was 41 months (range 1, 168). The most frequently reported clinical symptom was dyspnea (62.5%), followed by fever (25.0%), cough (16.7%), abdominal pain (8.3%), and chest pain (4.2%). Pleural fluid was typically described as white and milky in appearance (87.5%). Biochemical analysis revealed a median pleural fluid triglyceride concentration of 547.4 mg/dL and an albumin level of 4.4 g/dL. Dasatinib therapy was discontinued in 83.3% of patients. Alternative tyrosine kinase inhibitors were prescribed in selected cases, including nilotinib (33.3%), imatinib (20.8%), and bosutinib (16.7%). Supportive treatments consisted primarily of corticosteroids (45.8%), diuretics (45.8%), and thoracentesis (29.2%). Clinical improvement was observed in 91.7% of patients, with a median time to recovery of 12.2 weeks (range 1, 52). Among the four patients who underwent dasatinib rechallenge, three experienced recurrence of chylothorax.ConclusionDasatinib-induced chylothorax is rare but often reversible. Early diagnosis, drug discontinuation, and appropriate supportive care are key to recovery. Rechallenge should be undertaken cautiously due to a high risk of recurrence.